2011
DOI: 10.1007/978-3-642-23274-9_19
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor Agonists and Antagonists: Effects on Cancer

Abstract: Many epithelial and endothelial cells express a cholinergic autocrine loop in which acetylcholine acts as a growth factor to stimulate cell growth. Cancers derived from these tissues similarly express a cholinergic autocrine loop and ACh secreted by the cancer or neighboring cells interacts with M3 muscarinic receptors expressed on the cancer cells to stimulate tumor growth. Primary proliferative pathways involve MAPK and Akt activation. The ability of muscarinic agonists to stimulate, and M3 antagonists to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 78 publications
(97 reference statements)
3
71
0
Order By: Relevance
“…Many studies have demonstrated that ACh mainly acts through muscarinic receptors to transduce the exo-cellular signaling and plays an critical role in tumorigeneis2829. The muscarinic receptors contained five subtypes, including M1~5 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that ACh mainly acts through muscarinic receptors to transduce the exo-cellular signaling and plays an critical role in tumorigeneis2829. The muscarinic receptors contained five subtypes, including M1~5 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The mAChR are G-protein coupled receptors and there are 5 subtypes; M1, M3 and M5 are coupled to Gq and M2 and M4 are coupled to Gi. The majority of reports link the Gq coupled receptors to proliferation and evidence is particularly strong for a proliferative role of the M3 receptor in lung cancer and colon cancer [5860]. M3 receptors are a particularly intriguing target since M3 muscarinic receptor antagonists are in wide clinical use for overactive bladder [61] (eg, darifenacin and solifenacin) and COPD [62] (tiotropium, aclidinium, glycopyrronium) and are generally well tolerated.…”
Section: Muscarinic Signaling In Lung Cancermentioning
confidence: 99%
“…Muscarinic receptors are G-protein-coupled receptors consisting of five members, CHRM1-CHRM5 (5). Activation of muscarinic receptors triggers Ca 2þ influx, which causes smooth muscle contraction and glandular secretion.…”
Section: Introductionmentioning
confidence: 99%